2016
DOI: 10.1007/s11465-016-0393-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the tensile properties of friction stir welded aluminum alloy joints based on axial force, traverse speed, and rotational speed

Abstract: Friction stir welding (FSW) process has gained attention in recent years because of its advantages over the conventional fusion welding process. These advantages include the absence of heat formation in the affected zone and the absence of large distortion, porosity, oxidation, and cracking. Experimental investigations are necessary to understand the physical behavior that causes the high tensile strength of welded joints of different metals and alloys. Existing literature indicates that tensile properties exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 43 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Thus, further research may bring more insights into the relative importance of each practice. Fifth, although the PLS algorithm considers model complexity, discrepancies and uncertainties in the modelling process concerning structural parameters or measurement errors may allow for the application of other approaches that take these uncertainties into consideration [64,65] and compare the results to those mentioned in our study. Finally, upcoming research may use actual performance outcomes rather than self-reported or perceptual data when examining post-implementation practices to gain a true and substantial understanding of the impact of SMP.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, further research may bring more insights into the relative importance of each practice. Fifth, although the PLS algorithm considers model complexity, discrepancies and uncertainties in the modelling process concerning structural parameters or measurement errors may allow for the application of other approaches that take these uncertainties into consideration [64,65] and compare the results to those mentioned in our study. Finally, upcoming research may use actual performance outcomes rather than self-reported or perceptual data when examining post-implementation practices to gain a true and substantial understanding of the impact of SMP.…”
Section: Discussionmentioning
confidence: 96%
“…Out of several parameters of FSW, TTS plays the key role and is one of the most important parameters as per the industrial point of view and improves the productivity of FSW. It has been reported that efficiency-wise TTS imparts 35% attention to the mechanical strength of the joint [20]. The TTS influences the extent of specific heat input generated during welding to achieve the sound and smooth joint in FSW [21].…”
Section: Introductionmentioning
confidence: 99%
“…Optimization methods based on heuristic and/or biological solutions have been used in various problems. Panda, Garg, Jian, Heidarzadeh, and Gao () proposed genetic programming (GP) with three inputs and two outputs to model ultimate tensile strength and tensile elongation of aluminium alloy joints based on axial force, traverse speed, and rotational speed. Garg, Panda, and Lam () used two soft computing methods (gene expression programming and M5 model tree) to analyse fuel cell characteristic based on five input conditions of direct methanol fuel cells.…”
Section: Introductionmentioning
confidence: 99%